A68: The Role of Serum S100A12 Protein Levels in Maintaining Inactive Disease on Anti‐tumor Necrosis Factor Therapy in Polyarticular Forms of Juvenile Idiopathic Arthritis. Issue 11 (March 2014) - Hinze, Claas; Foell, Dirk; Johnson, Anne; Kimura, Yukiko; Spalding, Steven J.; Morris, Paula W.; Gottlieb, Beth; Onel, Karen; Olson, Judyann C.; Edelheit, Barbara; Shishov, Michael; Jung, Lawrence; et al.
Abstract : Background/Purpose: Treatment with anti‐TNF therapies for polyarticular forms (extended oligoarthritis, rheumatoid factor [RF] +/− polyarthritis) of JIA (PF‐JIA) results in up to 50% of patients (pts) demonstrating clinically inactive disease (CID). Serum S100A12 protein levels have been demonstrated to predict failure to maintain CID after withdrawal of methotrexate (MTX). This study determined the pattern of baseline serum S100A12 levels during CID on anti‐TNF therapy. Methods: In 16 centers, 137 pts with PF‐JIA in CID on anti‐TNF therapy were enrolled. During the first 6 study months patients were maintained on anti‐TNF therapy and monitored. If CID was maintained for first 6 study months, then anti‐TNF therapy was stopped. Pts were followed for up to 14 mos total or until loss of CID on anti‐TNF therapy or until flare off anti‐TNF therapy, whichever came first. Background medications were stable throughout the study. Blood for serum S100A12 measurement was drawn at study enrollment. S100A12 measurements were obtained via a validated ELISA. The secondary outcome of this part of the analysis was failure to maintain CID during the first 6 study months. Results: 7 pts were discontinued from the study for reasons other than inability to maintain CID and 130 patients were available for analysis. 24 pts failed to maintain CID during the first 6 study months. Demographic and clinical details are reported elsewhere during this conference. Baseline S100A12 levels did not differ significantly according to sex (female 96 +/− 229 ng/ml, male 66 +/− 144 ng/ml), JIA subtype (extended oligo 91 +/− 199 ng/ml, poly RF‐ 93 +/− 219 ng/ml, poly RF+ 114 +/− 157 ng/ml) presence of ANA (positive 83 +/− 174 ng/ml, negative 96 +/− 240 ng/ml), MTX co‐therapy (yes 84 +/− 259 ng/ml, no 95 +/− 167 ng/ml) or type of anti‐TNF therapy (adalimumab 114 +/− 140 ng/ml, etanercept 90 +/− 214 ng/ml, infliximab 120 +/− 330 ng/ml) (values given as median +/− standard deviation) and did not correlate with duration of previous duration of inactive disease (r = −0, 06). Globally, S100A12 did not differ significantly according to failure to maintain CID (failure to maintain CID 100 +/− 188 ng/ml, maintaining CID 93 +/− 216 ng/ml). Based on a predefined normal level of S100A12 of <120 ng/ml, 87 (66%) of patients demonstrated normal S100A12 levels and 43 (33%) of patients demonstrated elevated S100A12 levels. However, receiveroperating curve analysis computing baseline S100A12 against failure to maintain CID demonstrated an areaunder‐the‐curve of 0, 47 (95% confidence interval 0.33–0.62). Conclusion: In this prospective multicenter study, baseline S100A12 levels in pts with PF‐JIA were elevated in a substantial proportion of pts but did not differ among groups according to multiple parameters. Serum S100A12 did not predict failure to maintain CID.